Plant architecture and grain yield in common bean progenies with erect and prostrate plant habit - Silva, Camila Andrade; Abreu, Ângela de Fátima Barbosa; Ramalho, Magno Antonio Patto (Pesquisa Agropecuaria Brasileira, 2010)
The objective of this work was to evaluate if progenies with erect and prostrate plant habit, from the same genetic pool, have the same yield potential. Crosses between a prostrate and three erect cultivars were made yielding three populations up to the F5 generation. In this generation, erect and prostrate plants from each population were selected and evaluated in separate experiments. Generations F5:6, F5:7 and F5:8 were evaluated for plant architecture, in a scale from 1 (erect) to 9 (prostrate) and for grain yield. The expected gain for selection for plant habit and the correlated response in grain yield, as well as gain from selection for grain yield with the correlated response in plant habit were estimated. The correlation between selection for better plant habit and grain yield was low and negative. It is possible to select common bean progenies simultaneously for yield and plant habit.